2011
DOI: 10.1089/aid.2010.0333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of HIV Type 1 CRF02_AG in Cameroon and African Patients Living in Italy

Abstract: HIV-1 CRF02_AG accounts for > 50% of infected individuals in Cameroon. CRF02_AG prevalence has been increasing both in Africa and Europe, particularly in Italy because of migrations from the sub-Saharan region. This study investigated the molecular epidemiology of CRF02_AG in Cameroon by employing Bayesian phylodynamics and analyzed the relationship between HIV-1 CRF02_AG isolates circulating in Italy and those prevalent in Africa to understand the link between the two epidemics. Among 291 Cameroonian reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
4
11
1
Order By: Relevance
“…The dates that we inferred for the origin of CRF02_AG (1962 for PR and 1963 for gp41) are a decade older than estimates from previous studies (Abecasis et al, 2009;Faria et al, 2012) Our regional analysis of CRF02_AG shows that this viral variant expanded throughout West Africa showing a high degree of transmission between countries, demonstrated by the lack of clear migration routes and the phylogenetic intermixing of the sequences (also reported by (Véras et al, 2011)). This would agree with a fast spread of CRF02_AG in the region, and with the historical records of migration in West Africa: historically, this region has experienced a great mobility caused by population pressure, environmental conditions, poverty, and endemic conflicts.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The dates that we inferred for the origin of CRF02_AG (1962 for PR and 1963 for gp41) are a decade older than estimates from previous studies (Abecasis et al, 2009;Faria et al, 2012) Our regional analysis of CRF02_AG shows that this viral variant expanded throughout West Africa showing a high degree of transmission between countries, demonstrated by the lack of clear migration routes and the phylogenetic intermixing of the sequences (also reported by (Véras et al, 2011)). This would agree with a fast spread of CRF02_AG in the region, and with the historical records of migration in West Africa: historically, this region has experienced a great mobility caused by population pressure, environmental conditions, poverty, and endemic conflicts.…”
Section: Discussioncontrasting
confidence: 45%
“…According to previous reports, it seems to have travelled northwards from DRC, where its had been inferred (Faria et al, 2012) to Cameroon, which acted as the epicentre of its dispersal (Faria et al, 2012;Véras et al, 2011), and eventually to Nigeria where it was first identified (Carr et al, 1998). Our study provides the first analysis of the origin and dispersal of CRF02_AG to and within West Africa, where it is the prevalent HIV-1 variant.…”
Section: Discussionmentioning
confidence: 50%
“…A previous study proposed that CRF02_AG was introduced in Equatorial Guinea from Cameroon [24], but our results showed that only one of the 6 fell within Central African clades, being the rest related to Western African clades. In many cases, sequences from both regions were interspersed in the analysis ( Figure 1 ), which suggests a frequent circulation of CRF02_AG between countries, as others have also indicated [25]. In both Western and Central Africa the presence of this recombinant, originated at least in the early 1970s [24], has increased in the last years [6].…”
Section: Discussionmentioning
confidence: 76%
“…Sequence clustering is also used to infer historical links between epidemics in different geographic regions, such as Brazil, South Africa, South America and the UK [26–29]. More recently, phylogeographic methods have been applied to model the spread of such local epidemics within subtypes B, C, F and CRF02_AG populations [3033]. In some cases, within-subtype clustering has led to sub-subtype definitions, although these designations are limited by the nomenclature standard, which requires full-length genome sequences [5].…”
mentioning
confidence: 99%